Legal protection for investors in cases of illegal cryptocurrency-based investments in Indonesia - Pratama, Rizki; Angriani, Jum (Institute Of computer Science (IOCS), 2025)
Cryptocurrency-based investments in Indonesia are rapidly developing with advancements in digital technology, but illegal investment practices often harm investors. The low level of financial literacy and regulatory gaps are exploited to run illegal schemes such as Ponzi and multi-level marketing (MLM), as seen in the case of E-Dinar Coin. (EDC Cash). This research aims to analyze legal protection for investors in cases of illegal cryptocurrency investments in Indonesia. The method used is a normative juridical approach with a literature study and case study. The analysis was conducted on regulations such as the ITE Law and Bappebti Regulation Number 5 of 2019, as well as related court rulings. The research results show that the regulations have not been effective in protecting investors due to weak supervision, lack of synchronization between institutions, and the absence of a compensation mechanism. Strengthening regulations, strict supervision, and digital literacy education are needed to create a safe and transparent cryptocurrency investment ecosystem in Indonesia